2002
DOI: 10.1103/physrevb.66.235409
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic potential for adsorbate/surface systems: CO on Pt

Abstract: An atomistic interaction potential for adsorbate/surface systems is presented, based on the modified embedded-atom method ͑MEAM͒ and applied to CO on Pt. All parameters are determined using both densityfunctional theory ͑DFT͒ calculations, as well as the necessary experimental data. Whereas current DFT implementations suffer from problems in predicting the correct adsorption site of CO on Pt͕111͖, the current MEAM potential quantitatively describes the adsorption energies on the Pt ͕100͖ and ͕111͖ surfaces. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…Perhaps it is best to take the idea of embedding not too literally. This conclusion agrees with van Beurden and Kramer, 22 who argue that i should be interpreted as the effective coordination number of atom i, rather than as the local electron density, and F as a bond order correction function. Mishin et al 23 practically abandon all physical interpretation and consider the functions as mere fitting functions.…”
Section: Discussionsupporting
confidence: 80%
“…Perhaps it is best to take the idea of embedding not too literally. This conclusion agrees with van Beurden and Kramer, 22 who argue that i should be interpreted as the effective coordination number of atom i, rather than as the local electron density, and F as a bond order correction function. Mishin et al 23 practically abandon all physical interpretation and consider the functions as mere fitting functions.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, we have shown that molecular simulations using the modified embedded-atom method (MEAM) [18], are able to describe a wide range of surface properties of transition metals [19,20]. It is this method that, in terms of number of particles and time scale, allows in principle investigation of systems at the required scale, such as the adsorbate-induced lifting of a surface reconstruction.…”
mentioning
confidence: 99%
“…It is this method that, in terms of number of particles and time scale, allows in principle investigation of systems at the required scale, such as the adsorbate-induced lifting of a surface reconstruction. We have developed a potential parametrization for the CO=Pt system, based on DFT calculations as well as experimental data, that correctly takes into account the CO-CO lateral interaction and adsorption energies of CO at different surface sites on the (100) and (111) surfaces [20]. The adsorption energy of CO on the (100)-hex surface phase was, however, not included in the parameter fit data.…”
mentioning
confidence: 99%
“…69 This is an improvement over the pair potential and EAM schemes since it includes the effects of angular bonding in the embedding functions, albeit in an entirely empirical manner. While the MEAM formalism is significantly more computationally efficient than the BOP, this is at the expense of a significantly less rigorous relation to the fully quantum-mechanical description of interatomic bonding provided by TB methods.…”
Section: Discussionmentioning
confidence: 99%